Pengaruh Kualitas Pelayanan dan Semangat Kerja Terhadap Kepuasan Masyarakat dengan Kecerdasan Sosial Sebagai Variabel Intervening pada Kantor Camat Tilatang Kamang - Suwardi, Suwardi; Yulihasri, Yulihasri (Lembaga Intelektual Muda (LIM) Maluku, 2024)
The purpose of this research is to determine the influence of service quality and work enthusiasm on community satisfaction with social intelligence as an intervening variable at the Tilatang Kamang sub-district office. The method used is an analytical or reception survey with data analysis techniques of outer model testing, inner model testing and hypothesis testing. The sample was 100 residents of Tilatang Kamang District. The results obtained show that there is a positive and significant influence of service quality on social intelligence at the Tilatang Kamang District Head Office. There is a positive and significant influence of work enthusiasm on social intelligence at the Tilatang Kamang Subdistrict Office. There is a positive and significant influence of service quality on community satisfaction at the Tilatang Kamang District Head Office. There is a positive and significant influence of work morale on community satisfaction at the Tilatang Kamang District Head Office. There is a positive and significant influence of social intelligence on community satisfaction at the Tilatang Kamang District Head Office. Social intelligence is able to mediate the influence of service quality on community satisfaction at the Tilatang Kamang District Head Office. Social intelligence is able to mediate the influence of work morale on community satisfaction at the Tilatang Kamang District Head Office